Effect of cognitive and motor dual‐task on oropharyngeal swallowing in Parkinson's disease. (2nd December 2020) - Labeit, Bendix; Claus, Inga; Muhle, Paul; Regner, Liesa; Suntrup‐Krueger, Sonja; Dziewas, Rainer; Warnecke, Tobias
Abstract: Background: Dysphagia frequently occurs in patients with Parkinson's disease (PD) and is associated with severe complications. However, the underlying pathology is poorly understood at present. This study investigated the effect of cognitive and motor dual‐task interference on oropharyngeal swallowing in PD. Methods: Thirty PD patients (23 men, mean age 65.90 ± 9.32 years, mean Hoehn and Yahr stage 2.62 ± 0.81, mean UPDRS 18.00 ± 7.18) were examined using flexible endoscopic evaluation of swallowing (FEES). FEES was performed during three paradigms: at baseline without interference, during a cognitive dual‐task, and during a motor dual‐task. Oropharyngeal swallowing function was rated using a score which was validated to detect changes in PD related dysphagia. The three paradigms were compared using a two‐way‐repetitive‐measures‐ANOVA and a post‐hoc‐analysis. Results: Mean swallowing score in baseline FEES was 10.67 ± 5.89. It significantly increased (worsened) to 15.97 ± 7.62 ( p < 0.001) in the motor dual‐task and to 14.55 ± 7.49 ( p < 0.001) in the cognitive dual‐task. Premature bolus spillage and pharyngeal residue both significantly increased during both of the dual‐task conditions whereas penetration/aspiration events did not change. Conclusion: Oropharyngeal swallowing in patients with PD is not purely reflexive but requires mental capacity. Additional allocation of attentional resources in the central control of swallowing seems to be an effective compensatory mechanism in PD‐related dysphagia: The proposed dual‐task protocol may be useful to challenge swallowing functional reserve. Conversely, as a therapeutic strategy, it could be beneficial to focus attention on swallowing and to avoid dual‐task situations. Abstract : This study investigated the effect of cognitive and motor dual‐task interference on oropharyngeal swallowing in Parkinson's disease. Dual‐task significantly worsened oropharyngeal swallowing function. Additional allocation of attentional resources in the central control of swallowing seems to be an effective compensatory mechanism in Parkinson's disease related dysphagia.